Two new species of the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam and China - Nguyen, Lien Thi Phuong; Xu, Zaifu (Zootaxa, 2014)
Two new species are described and figured: Okinawepipona nigra Nguyen & Xu, sp. nov. (northern Vietnam and southern China), and O. curcipunctura Nguyen & Xu, sp. nov. (southern China). A key to the three known species of the genus is provided.